Pengaruh Muatan Bahan Peledak Dan Delay Peledakan Terhadap Tingkat Getaran Tanah Akibat Aktivitas Peledakan - Kasbillah; Agus Winarno; Lucia Litha Respati; Revia Oktaviani; Tommy Trides (Retii, 2023)
Blasting activities carried out in mining activities always produce effects that will have an impact on the surrounding area of the blasting site, from some of the blasting effects that exist one of which is soil vibration, so that at the research site in Pit Jongkang which is close to the village with a distance of approximately 300-400m it is very important to measure the level of vibration leading to the village so that the results of the vibration caused by the blasting process are obtained. Based on the results of the analysis obtained the effect of the explosive charge on the vibration of the soil that is the more the explosive charge of the resulting vibration will be greater. And with the holes that explode simultaneously, the vibration caused will be large so that the use of delay time is needed to minimize the presence of holes that explode simultaneously so that the resulting vibration does not exceed the 2 mm/s vibration limit. For recommendations on the maximum amount of explosive charge so that the vibration caused does not exceed the PPV standard, namely at a distance of 300 m, and 400 m by 36 kg, and 64 kg, perdelay. With the use of the recommended surface delay is a pair of surface delay 42 ms and 67 ms in the echelon cut circuit pattern, because it slightly efficiencies the time and the resulting PPV does not exceed 2 mm/s.